Perkawinan di Maroko - Nasiri Nasiri (STAI Syaichona Moh. Cholil Bangkalan, 2017)
Legal marriage in Morocco is not much different from the law of marriage in Islamic countries. Regulations related to marriage was almost the same with Indonesia, it dikarenan could be due to the Islamic Law Compilation (KHI) in Indonesia reflect to Mudawwanat al-Usrah in Morocco or it could be because society Morocco and the people on Indonesia equally homage to the Ahl al-Sunnah wa al -jama'ah (Aswaja), in Morocco Maliki that guide and in Indonesia Shafi'i school of being a role model. Morocco is not allowed to marry 'urfi (married Sirri). In addition to its urfi marriage was considered a disgrace, this type of marriage is prohibited by the laws of marriage Morocco.